(untitled) (Journal of Bangladesh Academy of Sciences, 2023)
The severity of the coronavirus disease 2019 (COVID-19) is linked to pro-inflammatory cytokine levels. There are still many unanswered questions regarding COVID-19 pathogenesis and prognosis. Significantly increased levels of pro-inflammatory cytokines characterize severe COVID-19 compared to those with a mild-to-moderate form of the disease. In this study, we used in silico tools to explore the variant allele frequency distributions of three important pro-inflammatory cytokine genes: interleukin-6 (IL-6), interleukin-8 (IL-8), and tumor necrosis factor-alpha (TNFA), as well as their linkage disequilibrium (LD) patterns in worldwide populations. These cytokines were chosen for their pro-inflammatory properties, importance in determining COVID-19 outcomes, and potential as disease treatment targets. Twenty-two of the variants correlate with altered cytokine expression levels, which may also influence the expression of several other mediators of immune responses. These variants also appear to be associated with several COVID-19 comorbidities, such as diabetes, asthma, obesity, and heart conditions. At least one variant (rs1800795 in IL6) is likely associated with an altered response to TNFA inhibitors, which are considered COVID-19 treatment options. The European super-population has high variant allele frequencies (VAF ≥ 0.2) at thirteen of these variant loci. High genetic heterogeneity at these loci is present in the admixed American populations, whereas the East Asian populations appear genetically more homogeneous. Interethnic differences are more pronounced at the IL6 SNP loci, which may cause variances in the expression level of a long non-coding RNA gene, IL6-AS1. Stronger and more extensive LD (R2 ≥ 0.8) exists among the IL6 and IL8 variants in the European super-population and among the TNFA variants in the East and South Asian populations. In general, the European super-population has higher frequencies of haplotypes with multiple variant alleles. Such interethnic differences may shed more light on the disparities in COVID-19 severities and the responses to treatments across ethnic groups. J. Bangladesh Acad. Sci. 47(1); 69-90: June 2023